2009
DOI: 10.1016/j.jfms.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Feline thyroid carcinoma: Diagnosis and response to high-dose radioactive iodine treatment

Abstract: This study reports the scintigraphy, histopathology, sole treatment with high-dose radioactive iodine and outcome of eight cases of feline thyroid carcinoma. Scintigraphic findings were variable and in 7/8 cases scintigraphic features could not reliably distinguish whether the thyroid tissue was malignant. Histopathology revealed typical criteria of malignancy in all cases, with mitotic activity described most frequently (7/8 cases), followed by infiltration of local tissues (4/8 cases). Cellular pleomorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 13 publications
1
48
0
3
Order By: Relevance
“…The scintigraphic imaging features that have been described for thyroid carcinomas are a heterogeneous uptake pattern with irregular, spiculated margins, a multifocal pattern with uptake outside the normal thyroid lobe margins, and a linear multifocal uptake pattern secondary to tumour extension along the fascial planes. 29,30 Although these imaging features are not highly reliable in differentiating malignant from benign disease, 30 none of the 16 persistent hyperthyroid cats in our study were suspected of malignant disease, based on their scans and follow-up. However, as no biopsies or fine-needle aspirates were taken, no final conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 76%
“…The scintigraphic imaging features that have been described for thyroid carcinomas are a heterogeneous uptake pattern with irregular, spiculated margins, a multifocal pattern with uptake outside the normal thyroid lobe margins, and a linear multifocal uptake pattern secondary to tumour extension along the fascial planes. 29,30 Although these imaging features are not highly reliable in differentiating malignant from benign disease, 30 none of the 16 persistent hyperthyroid cats in our study were suspected of malignant disease, based on their scans and follow-up. However, as no biopsies or fine-needle aspirates were taken, no final conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 76%
“…Approximately, 2% of hyperthyroid cats develop thyroid carcinoma, which can be classified as either follicular, papillary or mixed (Turrel et al 1988, Hibbert et al 2009). However, the prevalence of malignancy developing within a feline goiter appears to increase progressively over time, especially if the toxic goiter is not definitively treated with thyroidectomy or radioiodine (Peterson 2012, Broome & Peterson 2014, Peterson & Broome 2014a.…”
Section: Pathology Of Feline Toxic Nodular Goitermentioning
confidence: 99%
“…To the author ’ s knowledge, Bristol and Glasgow universities remain the only centres in the UK to carry a licence permitting the use of high-dose RI treatment. Additionally, a small study from the University of Bristol showed encouraging results of high-dose RI treatment as the sole treatment modality for thyroid carcinoma, with six of eight cats being cured and having lengthy survival times (Hibbert and others 2009). …”
Section: Carcinomasmentioning
confidence: 99%